2020
DOI: 10.12932/ap-070918-0403
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effect of nasal saline irrigation in children with allergic rhinitis and asthma: A randomized clinical trial

Abstract: Background: Asthma and allergic rhinitis (AR) are chronic inflammatory diseases of airway and affect the disease severity each other.Objective: We performed this study to examine whether nasal saline irrigation (NSI) improves bronchial hyperresponsiveness and clinical parameters in children with asthma and allergic rhinitis (AR). Methods:We enrolled 20 children with AR and asthma aged between 6-18 years. Patients were randomized into two groups: irrigation group (8 boys and 2 girls) and control group (8 boys a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 27 publications
(40 reference statements)
0
13
0
Order By: Relevance
“…Many devices (spray, atomizer device, or large-volume syringe) provided beneficial effects. Minor adverse events, such as otalgia, ear fullness, and epistaxis, occurred in 30% of the patients who used a large-volume device 15 but none in very low and low-volume devices. 17 , 19 - 21 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many devices (spray, atomizer device, or large-volume syringe) provided beneficial effects. Minor adverse events, such as otalgia, ear fullness, and epistaxis, occurred in 30% of the patients who used a large-volume device 15 but none in very low and low-volume devices. 17 , 19 - 21 …”
Section: Resultsmentioning
confidence: 99%
“…Eleven RCTs assessed adult AR, 4 - 14 and 8 RCTs assessed pediatric AR. 15 - 22 Three meta-analyses pooled the data from adult and pediatric AR, 1 , 3 , 23 and 1 meta-analysis examined data only from children. 24 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Topical medications with intranasal drug delivery devices (IDDD) have been widely indicated as possible therapeutics, 16 especially among patients with rhinitis (allergic or not), allergic rhinoconjunctivitis, rhinosinusitis, and nasal polyposis. In the specific case of rhinitis, glucocorticoids have been mentioned as the gold standard in improving patients' quality of life.…”
Section: Intranasal Drug Delivery Devices Are a Potential Contaminatimentioning
confidence: 99%
“…Symptomatic treatment consists of antihistamines and nasal steroids, while allergen immunotherapy is usually performed in more severe/persistent cases [3,4]-in any case, AR usually requires chronic treatment, which raises safety Page 2 of 11 Mitsias et al Clin Transl Allergy (2020) 10:9 concerns about protracted drug usage, leading to the quest for non-pharmacological approaches [5,6]. Among add-on treatments, nasal irrigation (NI) with saline solutions appears to be useful [7][8][9][10][11], as it does not need medical prescription and is considered safe for long-term use [7]. Normal saline is primarily used, although studies have shown increased effectiveness with hypertonic solutions [8,9].…”
Section: Introductionmentioning
confidence: 99%